In Situ Nanozyme‐Amplified NIR‐II Phototheranostics for Tumor‐Specific Imaging and Therapy. (1st July 2021) - Ma, Zhaoyu; Foda, Mohamed F.; Liang, Huageng; Zhao, Yanli; Han, Heyou
Abstract: The discovery of near‐IR‐II (NIR‐II) tumor phototheranostics holds a great promise for use in nanomedicine on account of its enhanced penetration depth, high spatial resolution, and noninvasiveness. However, contemporary "always on" phototherapeutic agents often have many undesirable side effects that hinder their clinical trial progress. To overcome this dilemma, an in situ nanozyme‐amplified chromogenic nanoreactor by loading 3, 3′, 5, 5′‐tetramethylbenzidine (TMB) and ultrasmall PtAu nanoparticles into a metal–organic framework is developed for specific tumor theranostics, leaving normal tissues unharmed. As an intelligent photoacoustic diagnostic agent, the as‐constructed nanoreactor remains silent until they enter the tumor site (H2 O2 ‐activated and acid‐enhanced conditions) and turns on the photoacoustic signal to render a preoperative tumor diagnosis. As a nanozyme, the special microenvironment of the tumor tissue is used to initiate its catalytic damage by reactive oxygen species for chemodynamic therapy (CDT). More importantly, the TMB is oxidized, and the subsequent photothermal therapy (PTT) can be realized, leading to an optimal combination of CDT and PTT to concurrently fight obstinate cancers. The present "all‐in‐one" phototheranostics utilize nanozyme‐augmented NIR‐II agents for specific tumor ablation, which are promising for further development of intelligent nanozymes in tumor therapy. Abstract : An in situ nanozyme‐amplified nanoreactor is developed by loading 3, 3′, 5, 5′‐tetramethylbenzidine and PtAu nanoparticles into a metal‐organic framework. The nanoreactor remains silent until they enter the tumor site and turns on the photoacoustic signal to render a preoperative tumor diagnosis. The nanoreactor can also realize chemodynamic and photothermal therapy for concurrent tumor therapy.